Advances in enterprise information technology security - Khadraoui, Djamel; Herrmann, Francine (Hershey PA : Information Science Reference, 2007)
"This book provides a broad working knowledge of all the major security issues affecting today's enterprise IT activities. Multiple techniques, strategies, and applications are thoroughly examined, presenting the tools to address opportunities in the field.It is an all-in-one reference for IT managers, network administrators, researchers, and students"--Provided by publisher.
Ηλεκτρονικό βιβλίο
Keywords: Business enterprises -- Computer networks -- Security measures; Information technology -- Security measures; Computer security; Data protection; Electronic books